Second Holcim Awards : Regional and global holcim axards competitions for sustainable construction projects and visions 2008/2009 (Holcim Foundation for Sustainable Construction, 2009)
Contextual government quarter development. Budapest, Hungary - Temporary urban extension in a former landfill. Maribor, Slovenia - Autonomous alpine shelter. Monte Rosa hut Zermatt, Switzerland - Culturally-responsive urban village. Belgrade, Serbia - Low-cost residence on industrial site. Ghent, Belgium - Office building with green hypercore. Milan, Italy - Waterfront reclamation and remediation. Southern Italy - Production and ecological cluster. New Haven, UK - Urban greening and economic catalyst. Madrid, Spain - Self-sufficient rural community. Paimio, Finland - Solar 2 green energy, arts and education center. New York, USA - Self-contained day labor station. San Francisco, USA - Living with lakes center for freshwater restoration and reserch. Sudbury, Canadá - Evergreen brick works heritage site revitalization. Toronto, Canadá - Minimal-impact north Vancouver outdoor. School, Canadá - Strategy for environmentally-friendly integration of beehives. Detroit, USA - Microstructure research for building skins. Cambridge, USA - Residential density for urban spaces. Toronto, Canadá - Responsive urban downtown activity center. Boston, USA - Urban integration of an informal area. Medellín, Colombia - Low-energy university mediatheque. Río de Janeiro, Brazil - Solar water heating and rainwater tower. Florianópolis, Brazil - Ecological river remediation park. Morelia, México - Energy.efficient medical and social center. Sao Paulo, Brazil - Mountain trail for land preservation and urban demarcation. Bogotá, Colombia - Multi-modal transport hub upgrade. Río de Janeiro, Brazil - Post-earthquake reconstruction. San Lorenzo of Tarapacá, Chile - Sanitation and river remediation. Tuxtla Gutiérrez, México - Coastal forg-harvesting tower. Huasco, Chile - Eutropia low-cost and space-efficient social housing. México City, México - Agriculture facility for inner-city voids. Campinas, Brazil - River remediation and urban development scheme. Fez, Morocco - Low-cost school and home for HIV orphans. Rakai, Uganda - Lighthouse tower with low-carbon footprint. Dubai, UAE - Low-impact environmentally-responsive house. Cape Town, South Africa - School infrastructure from local resources. Vele and Vryheid, South Africa - Stabilized earth visitors' center. Mapungubwe National Park, South Africa - TunaHAKI integrated theater and orphanage. Moshi, Tanzania - Xeritow responsive urban planning strategy. Dubai, UAE - Amphibious dwellings in informal settlements. Lagos, Nigeria - Dune anti-desertification architecture. Sokoto, Nigeria - Waterfront sustainable development concept. Mombasa, Kenya.